The use of Keratin in biomedical applications - Vasconcelos, Andreia (2013)
Keratins are naturally derived proteins that can be fabricated into several biomaterials morphologies including films, sponges and hydrogels. As a physical matrix, keratin biomaterials have several advantages of both natural and synthetic materials that are useful in tissue engineering and controlled released applications. Like other naturally derived protein biomaterials, such as collagen, keratin possess amino acid sequences, similar to the ones found on extracellular matrix (ECM), that may interact with integrins showing their ability to support cellular attachment, proliferation and migration. The ability of developing biomaterials that mimic ECM has the potential to control several biological processes and this is the case for keratin which has been used in a variety of biomedical applications due to its biocompatibility and biodegradability. This review describes the progress to date towards the use of keratin in the field of wound healing, tissue engineering and drug delivery applications, with highlight to reports of particular relevance to the development of the underlying biomaterials science in this area.